FREELANCE. - FIELD, DOUGLAS (TLS. Times Literary Supplement, 2016)
A personal narrative is presented which explores the author's experience of spending eighteen months together with his friend, of putting an exhibition of the archive of Jeff Nuttall, an English poet, publisher, actor, painter, sculptor, jazz trumpeter, anarchist sympathiser and social commentator, friend Jay Jeff Jones.